PENGEMBANGAN E-MODUL LITERASI NUMERASI MATEMATIKA MI BERBASIS REALISTIC MATHEMATICS EDUCATION - Cahya Amalia Chusna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop a numeracy literacy e-module for Madrasah Ibtidaiyah students based on the principles of Realistic Mathematics Education (RME). The development process employed the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The e-module was designed to address students’ difficulties in understanding mathematical concepts, particularly in contextual problem-solving, and to provide interactive digital learning media aligned with the cognitive characteristics of Phase B learners. Data were collected through expert validation sheets, student and teacher response questionnaires, and pre-test and post-test assessments. The validity results indicated that all aspects of the e-module met the “valid” criteria, with expert judgment scores ranging from 88.57% to 97.14%. Practicality analysis also showed positive responses, categorized as “good” and “very good.” The effectiveness test using N-Gain revealed moderate improvement in the experimental classes (0.40 and 0.39) and low improvement in the control classes (0.18 and 0.12). Independent sample t-tests further confirmed significant differences in numeracy achievement between experimental and control groups (Sig. = 0.000). These findings demonstrate that the RME-based e-module is valid, practical, and effective in improving numeracy literacy among MI students, making it a promising digital resource for mathematics learning.